A Pilot Study of Reduced Olfactory Bulb Volume as a Marker of PTSD in Childhood Trauma‐Exposed Adult HIV‐Infected Patients. Issue 5 (27th October 2017) - Nwulia, Evaristus A.; Rai, Narayan; Sartip, Kamyar; Hipolito, Maria Mananita S.; McLean, Charlee K.; Flanagan, Kyla; Hamilton, Flora; Lambert, Sharon; Le, Huynh‐Nhu; VanMeter, John; Kapetanovic, Suad
Abstract: Evidence suggests that olfactory bulb (OB), a key structure in odor processing, may also be involved in mechanisms of traumatic stress. In animals, chronic stress reduces OB plasticity, and olfactory bulbectomy results in stress‐enhanced startle reflex and autonomic dysregulation. However, OB morphometry has not been adequately studied in the development of stress disorders following childhood trauma in humans. The researchers conducted a pilot study evaluating the relationships between OB volume, childhood trauma, and lifetime posttraumatic stress disorder (PTSD) in a sample of 16 HIV‐positive individuals, 13 of whom were exposed to childhood trauma of 9 developed PTSD. Participants were recruited from a larger cohort of inner city–dwelling HIV‐positive populations in Washington, DC. Mean OB volumes were significantly reduced when PTSD and non‐PTSD groups were compared, p = .019, as well as when trauma‐exposed PTSD‐positive and trauma‐exposed PTSD‐negative groups were compared, p = .008. No significant difference was observed when trauma‐exposed and nonexposed participants were compared. The association between PTSD and right OB volume remained strong p = 0.002 after adjusting for group differences in sex, age, depression, hippocampal volume, and total intracranial volume. Because this study is limited by small sample size, further elucidation of relationships between OB, trauma, and PTSD should be investigated in larger cross‐sectional and prospective studies and in diverse cohorts.